PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL PEMODERASI - Ega Wibi Prakoso; Darsono Darsono (Diponegoro Journal of Accounting, 2016)
This study is investigate the influence of Corporate Social Responsibility disclosure and managerial ownership as proxy from Good Corporate Governance to relationship between ROA as proxy from financial performance and firm value.The sample of this research is manufacture firm which is listed on Indonesia Stock Exchange (IDX) over 2012-2014. The research samples are 199 observations. The analysis methods of this research used multiple linear regression analysis for hypothesis 1 and multiple regression analysis with the Moderated Regression Analysis (MRA) for hypothesis 2 and 3.The results show three conclusions. The first analysis explains that ROA has significant influence to firm value. The second analysis explains that CSR disclosure is able to moderate the relationship between ROA and firm value. The third analysis explains that managerial ownership aren’t able to moderate the relationship between ROA on firm value. And then, the final conclusion in this study from variables which can be used to examine the relationship between ROA on firm value is CSR disclosure who strengthen the relationship between this two variables.